2011
DOI: 10.4220/sykepleienf.2011.0191
|View full text |Cite
|
Sign up to set email alerts
|

Norske sykepleieres kunnskap om og holdning til smerte hos barn

Abstract: Norske s kepleieres kunnskap om og holdning til smerte hos barn Emneord: Nøkkelord, Barn, Kunnskapsbasert sykepleie, Smerte Sykepleien Forskning 2011 6(4):332-339. Engelsk sammendrag:Norwegian nurses' knowledge and attitudes regarding pain and pain relief in children Background:Pain in children is underestimated and undertreated. Nurses attitudes and lack of knowledge are internationally reported as major causes of insufficient treatment of pain. Objective:To survey Norwegian paediatric nurses knowledge and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
1
0
0
Order By: Relevance
“…Most of the knowledge and attitude items concerning pain assessment were answered correctly by the nurses. Similar results were found in two other studies (Hovde, Granheim, Christophersen, & Dihle, 2011;. However, we found a gap between nurses' responses in the PNKAS-N and what they were observed practicing in relation to the use of pain assessment tools.…”
Section: Pain Assessmentsupporting
confidence: 89%
“…Most of the knowledge and attitude items concerning pain assessment were answered correctly by the nurses. Similar results were found in two other studies (Hovde, Granheim, Christophersen, & Dihle, 2011;. However, we found a gap between nurses' responses in the PNKAS-N and what they were observed practicing in relation to the use of pain assessment tools.…”
Section: Pain Assessmentsupporting
confidence: 89%
“…Results from PNKAS studies of nurses conducted in the Kingdom of Saudi Arabia (83), Ghana (84,85), Turkey (76), Mexico (13,87), Egypt (97), China (88), Mongolia (95) and Iran (98) showed low total mean scores, with < 50% correct answers. Studies conducted in the USA (12, 78-80, 96, 99), Canada (14,15,94), Norway (77), Spain (86) and Germany (81) showed higher total mean scores, with 56-82% correct answers. None of these studies, except one (14), found a mean score of > 80%, which is often set as the acceptable level of knowledge (84).…”
Section: Nurses' Knowledge and Attitudes Regarding Pediatric Painmentioning
confidence: 92%
“…Previous studies have shown that nurses have poor knowledge about and attitudes toward basic pediatric pain assessment and management principles (9). Nurses' knowledge and attitudes regarding pediatric pain management have been identified using the Pediatric Nurses' Knowledge and Attitude Survey Regarding Pain (PNKAS) in several previous studies (76)(77)(78)(79)(80)(81), conducted on nursing students (82), used in intervention studies (12)(13)(14)(15), and in more recent studies (83)(84)(85)(86)(87)(88) on nursing students (89)(90)(91)(92)(93), and in intervention studies (94)(95)(96)(97)(98)(99).…”
Section: Nurses' Knowledge and Attitudes Regarding Pediatric Painmentioning
confidence: 99%
See 1 more Smart Citation